Filmes nanométricos de FeN e ALN crescidos por sputtering e aplicações do efeito peltier - Moura, José Américo de Sousa (2010)
This study will show the capability of the reactive/nonreactive sputtering (dc/rf) technique at low power for the growth of nanometric thin films from magnetic materials (FeN) and widegap semiconductors (AlN), as well as the technological application of the Peltier effect using commercial modules of bismuth telluride (Bi2Te3). Of great technological interest to the high-density magnetic recording industry, the FeN system represents one of the most important magnetic achievements; however, diversity of the phases formed makes it difficult to control its magnetic properties during production of devices. We investigated the variation in these properties using ferromagnetic resonance, MOKE and atomic force microscopy (AFM), as a function of nitrogen concentration in the reactive gas mixture. Aluminum nitride, a component of widegap semiconductors and of considerable interest to the electronic and optoelectronic industry, was grown on nanometric thin film for the first time, with good structural quality by non-reactive rf sputtering of a pure AlN target at low power (≈ 50W). Another finding in this study is that a long deposition time for this material may lead to film contamination by materials adsorbed into deposition chamber walls. Energy-dispersive X-ray (EDX) analysis shows that the presence of magnetic contaminants from previous depositions results in grown AlN semiconductor films exhibiting magnetoresistance with high resistivity. The Peltier effect applied to commercially available compact refrigeration cells, which are efficient for cooling small volumes, was used to manufacture a technologically innovative refrigerated mini wine cooler, for which a patent was duly registered